Development of LKPD based on Higher Order Thinking Skills (HOTS) in Improving the Learning Outcomes of PAI Vs (Study at SDN 2 Cimari and SDN 1 Darmacaang Regency Ciamis - Iwan Setiawan; Nai Nor Fadilah; Iman Hidayatul Ulumi; Siti Zamroh; Dede Aji Mardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research is motivated by the use of learning devices that have not been maximized. The module used is only to explain the learning material, while the process to find out the extent of students' understanding is limited to question and answer activities and working on questions. This makes researchers want to develop Student Worksheet (LKPD) based on Higher Order Thinking Skills (HOTS) as a support for students' learning. The purpose of this study is to analyze the process of developing LKPD based on Higher Order Thinking Skill (HOTS) in improving the learning outcomes of PAI Classes V in SDN 2 Cimari and SDN 1 Darmacaang Ciamis Regency. This research uses the Borg and Gall research model. This research and development was conducted on class V students in SDN 2 Cimari and SDN 1 Darmacaang Ciamis Regency. The results of this study and development indicate that: (1) the development of LKPD -based HOTS begins by preparing learning material in accordance with learning achievements and the flow of learning objectives that have been listed in the independent curriculum. Furthermore, researchers make examples of hots questions that are in accordance with the material that has been presented, make problems of individual and group practice and then make competency test questions at the end of the chapter. (2) There is an influence of the use of HOTS -based LKPD is indicated by a significant difference in learning outcomes between experimental classes that conduct learning using HOTS -based LKPD with control classes that do learning without LKPD based on HOTS. Then it can be concluded that there is a significant influence between the experimental class that conducts teaching using LKPD based on Higher Order Thinking Skills (HOTS) with the control class that conducts teaching without using LKPD based on Higher Order Thinking Skills (HOTS) on the learning outcomes of PAI students of class V students